2004
DOI: 10.1080/14015430410001033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ‘open throat’ technique on vibrato rate, extent and onset in classical singing

Abstract: Mitchell, Kenny et al. (2003) identified 'open throat' as integral to the production of an even and consistent sound in classical singing. In this study, we compared vibrato rate, extent and onset of six advanced singing students under three conditions: 'optimal' (O), representing maximal open throat; 'sub-optimal' (SO), using reduced open throat; and loud sub-optimal (LSO), using reduced open throat but controlling for the effect of loudness. Fifteen expert judges correctly identified the sound produced when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
2
30
1
2
Order By: Relevance
“…61 From an acoustical point of view, there is no advantage of coupling the nose with the vocal tract because it results in damping of the sound, which is the opposite of the desired effect, 62 and, from an articulatory standpoint, the velopharyngeal port should be closed for the production of all vowels and nonnasal consonants. However, some authors remain adamant that some nasal/oral coupling is appropriate in singing, 63 and one study has shown that, in the participants measured, some nasality was present during singing nonnasal vowels. 64 The question as to the effect of the FFL through the velopharyngeal port has been raised previously.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…61 From an acoustical point of view, there is no advantage of coupling the nose with the vocal tract because it results in damping of the sound, which is the opposite of the desired effect, 62 and, from an articulatory standpoint, the velopharyngeal port should be closed for the production of all vowels and nonnasal consonants. However, some authors remain adamant that some nasal/oral coupling is appropriate in singing, 63 and one study has shown that, in the participants measured, some nasality was present during singing nonnasal vowels. 64 The question as to the effect of the FFL through the velopharyngeal port has been raised previously.…”
Section: Discussionmentioning
confidence: 97%
“…[55][56][57] Many terms are used by those in this field, but there is little agreement on what features are important in good vocal quality or what terms should describe these features. As a result, no standardized perceptual tool is available for the evaluation of the singing voice; this is interesting considering that the evaluation of the singing voice is traditionally perceptual.…”
Section: Discussionmentioning
confidence: 99%
“…Existen estudios que asocian esta técnica con el vibrato. Es así como Mitchell 12 encontró que el extent y onset se ven afectados por el grado de utilización de la "garganta abierta". Al no hacer uso de esta técnica ambos parámetros fueron mayores y fuera de los rangos aceptados como adecuados.…”
Section: Figura 7 -"Espectrograma Banda Estrecha Del Comienzo Del Ariunclassified
“…Otro rasgo acústico del vibrato es el "onset", el cual es considerado como el tiempo en segundos que tarda el inicio de la primera oscilación del vibrato desde que partió la emisión de sonido. Estudios asocian el retardo del inicio vibrato (mayor a 0,5 segundos) con una percepción de un vibrato pobre y esto también es altamente correlacionado con una pobre calidad de la voz en el canto 11,12 . Otros autores indican que mientras más temprano es el vibrato onset, más amplio es el extent 6 .…”
Section: Introductionunclassified
“…Mitchell et al,4 in subsequent studies, compared the open throat technique (O) with a reduction of the technique described as suboptimal (SO) in the same advanced singing students and found that experts could identify the technique in 83% of samples. 7,8 Applied research in voice must address the goals of singing pedagogy in assessing and refining a voice of quality and generate perceptually viable measures to systematically define voice. Ideally, we need exemplars of vocal quality and to find measurements that enable us to rank voices in accordance with acoustic measures.…”
Section: Introductionmentioning
confidence: 99%